Congenital isolated asplenia accidentally discovered during acute peritonitis - Abdelouhab, Elmarouni; Azız, Karam; Ouzzanı, Et-Tayeb; Zerhounı, Ahmed; Souıkı, Tarik; Ibn Majdoub El Hassanı, Karim; Mazaz, Khalid; Toughraı, Imane (Journal of Surgery and Medicine, 2020)
An extremely rare condition, congenital asplenia has 2 distinct types: heterotaxy syndromes and isolated congenital asplenia (ICA). Ivemark syndrome is one of the heterotaxy syndromes characterized by asplenia, malformations of the heart, and malposition of internal organs in the chest and abdomen. ICA cases are also fatal in childhood, but there are reported living adult cases. Those affected are typically at increased risk for fulminant sepsis and carry a higher risk of noninfectious complications, such as thrombocytosis and mesenteric thrombosis. We herein report the unusual case of a patient with congenital asplenia, which was discovered fortuitously during an emergency laparotomy for peritonitis due to ulcer perforation.